Utilization of Carbohydrates in Bamboo Shoots (Dendrocalamus asper) As an Alternative Media for the Growth of Candida albicans fungus - Bastian; Firna Nuha; Maria Ulva; Rossa Veronneca (Universitas PGRI Palembang, 2023)
Candidiasis disease caused by the fungus Candida albicans is a health problem in Indonesia. The chronic nature of the disease gets worse if it is accompanied by a fungal infection, which usually goes undiagnosed and untreated. Culture techniques can be used to identify the fungus Candida albicans. Mushroom culture in the laboratory requires a medium containing nutrients such as a carbohydrate source and a nitrogen source for growth. These nutrients can be found in bamboo shoots which contain high carbohydrates, protein, fat, vitamins, and crude fiber. So that bamboo shoots can be used as raw material for alternative mushroom growth media. The purpose of this study was to utilize bamboo shoots as a medium for the growth of Candida albicans herbal medicine. This research included collecting bamboo shoots, making rice bran media, inoculation of Candida albicans fungus on bamboo shoots media, and observing fungal growth. Candida albicans fungal colonies were confirmed by macroscopic and microscopic observations. The results showed that the fungus Candida albicans grew on both media, namely Bamboo Shoots Flour Media and Sabouraud Dextrose Agar (SDA) media at 37oC for 48 hours. The conclusion of this study is that bamboo shoots media can be used as a medium for fungal growth. Bamboo shoots media can be used as an alternative medium for synthetic media to grow Candida albican